The effect of national school health strategy components on the quality of health services: An Analytical research in Baghdad Governorate - Mohammed Kadhim Mohammed Ali*, Sama; Ismaeel Jabbouri Alqammach, Nada (Journal of Economics and Administrative Sciences, 2024)
Purpose: The research objective is to diagnose the extent to which the National School Health Strategy contributes to the quality of health services. Theoretical framework: The quality of health services can provide schools with benefits through building a healthy school community in line with the sustainable development goals, especially regarding quality education, good health, and well-being and through school health, we may be improving the health and well-being of elementary and secondary students, and the necessity of providing healthy foods reduction of fat content in school meals, and awareness to prevent the use of tobacco products and drugs. Design/methodology/approach: The research relied on the descriptive -analytical method and the research sample is a random sample of primary schools (governmental and private). The research tool is represented by using a questionnaire to collect data. Findings: Although there is a big school community represented by students compared to their society, studies in most countries of the world are still limited in discussing the quality of health services provided to them and the limited solutions. Research, Practical & Social implications: We suggest future research to evaluate the national school health strategy: a comparative study between two governorates. Originality/value: The results indicate that commitment to implementing school health programs positively affects the quality of health services provided to students of school age and that any defect in their application reflects negatively on the health of students currently and society in the future.